Age-Associated Tooth Loss and Oral Microbial Dysbiosis in a Mouse Genetic Model of Chronic Nicotine Exposure - Rogers, Scott W.; Myers, Elizabeth J.; Gahring, Lorise C. (Frontiers in Immunology, 2020)
Nicotine acts as a potent modulator of normal cellular responses through the nicotinic acetylcholine receptor subtype alpha7. In a mouse genetic model of alpha7 receptor dysfunction, alpha7E260A:G, 85 percent of 18 month-old mice exhibit an age-associated spontaneous loosening or complete loss of 3rd molars that was not present in the control mice. The adjacent soft tissues appeared largely unaffected. Further analysis including micro-CT revealed evidence of bone loss surrounding the 3rd molars with areas of cavitation and/or sponge-like (cancellous) bone remodeling in the mandible. The mandible microbiome was examined using 16S-rRNA sequencing. The results show the alpha7E260A:G oral microbiome included increased landscape complexity indicative of dysbiosis, and a significant increase of some bacteria, particularly Staphylococcus. These results suggest that normal alpha7 function plays a relevant role in maintaining normal gene expression and oral microbiome stasis. Consequently, this mouse model suggests there are consequences to ongoing alpha7 receptor dysfunction and oral health, as can occur from chronic exposure to nicotine as expected from electronic nicotine delivery systems (ENDS or 'vaping'), may not be seen until older age.